The individual empowerment Index (IEI): A new approach for empowerment measures - Kinkingninhoun Medagbe, F.M.; Floquet, A.; Mujawamariya, G.; Mongbo, R.L. (SAGE Publications, 2023)
Over the last three decades, many research works have been conducted to define and measure the complex and composite concept of empowerment. However, an individual empowerment tool is still needed, to be applied for any disadvantaged group, women, youths (male or female), poor, etc., or any economic sector, and which can be more suitable for rigorous impact assessment studies. This paper contributes to the growing empowerment literature by providing a new multi-domain, survey-based empowerment measurement tool, the individual empowerment index (IEI). The IEI is unique in its characterization and construction. It combines individual empowerment scores in six empowerment domains: production, household livelihood, resources, income, leadership, and time allocation. It is a flexible and survey-based empowerment parameter that can be generated at individual, household community or country levels, or for any target social category. The IEI is constructed through a specific methodology based on a scale survey with an ordinal variable principle and a general process for construction of domain indicators. A key advantage of the IEI is that different household members (even husband and wife) can have different IEIs and statuses. Findings from applying the IEI approach to data collected from 1120 West-African lowland rice farmers show that lowland rice farmers globally achieved on average 71% of their full empowerment potential with only 40% of them found to be globally empowered. Female farmers were found to have lower control over their lives and were less than male farmers to be empowered. IEI estimates and comparison between WIEI and other women empowerment indexes estimates show reasonable correspondence despite the difference in the methodology and can hold for the validity of the IEI. The new IEI is a suitable tool and is recommended for quantitative and rigorous impact assessment and monitoring of programs and projects empowerment indicators.